Copper‐Mediated Aromatic 1, 1‐Difluoroethylation with (1, 1‐Difluoroethyl)trimethylsilane (TMSCF2CH3). Issue 12 (1st June 2016) - Li, Xinjin; Zhao, Jingwei; Wang, Yunze; Rong, Jian; Hu, Mingyou; Chen, Dingben; Xiao, Pan; Ni, Chuanfa; Wang, Limin; Hu, Jinbo
Abstract: A new method for the formation of 1, 1‐difluoroethyl copper species ("CuCF2 CH3 ") with 1, 1‐difluoroethylsilane (TMSCF2 CH3 ) has been developed. The "CuCF2 CH3 " species can be applied to the efficient 1, 1‐difluoroethylation of diaryliodonium salts under mild conditions, affording (1, 1‐difluoroethyl)arenes in good to excellent yields. This convenient procedure tolerates a wide range of functional groups and thus serves as a practical synthetic tool for the introduction of CF2 CH3 group(s) into complex molecules. Abstract : Difluoroethylation under mild conditions : A new method for the formation of 1, 1‐difluoroethyl copper ("CuCF2 CH3 ") with 1, 1‐difluoroethylsilane (TMSCF2 CH3 ) has been developed. This copper reagent can be applied to efficient 1, 1‐difluoroethylation of diaryliodonium salts under mild conditions, affording (1, 1‐difluoroethyl)arenes in good yields. A difluoroethyled naproxen derivative was successfully synthesized by using this method.